Analisis Kesiapan dan Pengembangan Promosi Digital untuk Meningkatkan Daya Saing : Studi Kasus Florina Bouquet - Safira Nurhaliza; Jasmine Nashwa Mutiara Seno; Chikita Alamanda Arafa; Niken Dwi Astuti; Dina Mayasari Soeswoyo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the level of digital readiness and the development of digital promotion strategies at Florina Bouquet MSME as an effort to enhance competitiveness in the digital era. The research background arises from the limited optimiof Instagram features and digital marketing strategies, resulting in low product visibility in the digital market. This study employs a qualitative descriptive approach with data collected through observation, in-depth interviews, and literature review. A scoring analysis was applied to evaluate three main components: digital readiness, digital marketing strategy and implementation, and their impact on competitiveness. The findings indicate that Florina Bouquet demonstrates a relatively high level of digital readiness in terms of infrastructure and basic platform utilization; however, weaknesses remain in strategic planning, content creation, feature optimization, and consistent monitoring. Despite these limitations, the uniqueness of the product and strong market potential contribute positively to competitiveness, especially in differentiation and brand perception. The results highlight the need for more structured, consistent, and data-driven digital promotion strategies to improve marketing effectiveness and expand market reach. This study provides practical implications and strategic recommendations for MSMEs to strengthen their digital marketing performance sustainably.